Electrospinning process for green polymeric nanomaterials - Nurfaizey, A. H.; Juhana, Jaafar; Nadzirah, Mohd Mokhtar; Nik Abdul Hadi, Md Nordin (Elsevier, 2021)
Over the past few decades, research into nanomaterials has been one of the most popular topics in nanotechnology. To date, nanomaterials have found their potential uses in various fields of research and industry, mainly attributed to their unique physical and chemical properties. Electrospinning is the most widely used method for producing polymeric fiber-like nanomaterials. A wide range of synthetic polymer materials have been successfully electrospun into nanofibers. However, recently, growing concerns about the overuse of nonrenewable resources has triggered new studies on green polymers. In this chapter, relevant studies on green polymer electrospun fibers are reviewed. This includes natural polymers such as cellulose, chitin, lignin, protein, and synthetic bio-based polymers such as polylactic acid and polyhydroxyalkanoate. The use of related polymer-solvent systems and process paramaters is also reviewed. Due to their biocompatibility, biodegradability, and nontoxicity, biopolymer-based electrospun fibers have been proposed for various potential applications, especially in biomedical applications.